EDUCATIONAL LEADERSHIP IN SUPPORTING THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM: A QUALITATIVE STUDY AT SDN 01 KARANGPUCUNG - Ridha Trenafita; Ahmad Mufti Azkia; Zhafira Nur Fadilah; Aleeyah Dzatul Haqiqah Al Asari (PT. LITERASI SAINS NUSANTARA, 2026)
This study examines how educational leadership supports the implementation of the Independent Curriculum at SDN 01 Karangpucung, Indonesia. A descriptive qualitative approach was employed using semi-structured interviews, observations, and document analysis. The principal served as the primary informant, while six teachers provided supporting perspectives. Data were analyzed through data reduction, data display, and conclusion drawing, with triangulation used to enhance credibility. The findings indicate that the principal integrates managerial, instructional, transformational, and supervisory leadership to facilitate curriculum implementation. Competency-based teacher workload allocation, continuous instructional guidance, collaborative professional practices, and systematic curriculum evaluation contribute to improving teaching quality and curriculum implementation. However, challenges remain, particularly students' varying literacy abilities and inconsistent parental involvement. The study concludes that an integrated leadership approach is essential for effective curriculum implementation and sustainable school improvement. These findings provide practical insights for school leaders in strengthening curriculum reform through adaptive leadership and collaborative educational practices.